Improving minituber production from tissue-cultured potato plantlets with aeroponic technology in Uganda. - Kakuhenzire, R.; Tibanyendera, D.; Kashaija, I.N.; Lemaga, B.; Kimoone, G.; Kesiime, V.E.; Otazu, V.; Ortíz, O.; Barker, I. (2017)
Seed accounts for a significant proportion of potato production cost and its quality cannot be compromised for profitable potato production. Potato is conventionally vegetatively propagated, has a low multiplication rate and requires many generations to bulk the requisite seed quantity often in open fields. During seed bulking, the crop is prone to degeneration leading to successive loss in yield as a result of viral, bacterial and fungal infections. To reduce this, there should be few open field seed bulking generations before the stock is used for ware potato production. Rapid bulking of seed potato has not been possible due to its inherent low multiplication rate. However, this can be partly overcome by tissue culture, micro-propagation and deployment of novel technologies such as aeroponics to produce mini-tubers. Consequently, aeroponic technology for rapid production of nuclear seed was tested in Uganda for adaption in different seasons and with different varieties to produce potato mini-tubers. Production of mini-tubers was affected by cropping seasons and potato varieties. Generally, however, the performance of local potato varieties in aeroponics is promising. More mini-tubers per plantlet were produced at low than high plantlet density, while more mini-tubers per unit area were produced at high than low plantlet density. Preliminary results indicated that aeroponics on average produces 8.5 times more mini-tubers than the conventional soil substrates. The technology has shown a high potential to break the seed potato bottle-neck in Uganda.